2014
DOI: 10.1111/jbi.12329
|View full text |Cite
|
Sign up to set email alerts
|

Reduced parasite diversity and abundance in a marine whelk in its expanded geographical range

Abstract: Aim To improve our understanding of how parasitism interacts with geographical range expansions by quantifying diversity and abundance of parasites in 25 populations of a large marine snail, Kellet's whelk (Kelletia kelletii), throughout its historical and recently expanded range, which are separated by a well‐known biogeographical boundary. Location California coast (western North America). Methods Parasitological examinations were conducted on 199 whelks from 25 subtidal reefs throughout its expanded and his… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
17
0

Year Published

2015
2015
2023
2023

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 20 publications
(18 citation statements)
references
References 53 publications
0
17
0
Order By: Relevance
“…; Hopper et al . ). However, our categorization of fungal taxa as plant pathogenic was relatively coarse (i.e.…”
Section: Discussionmentioning
confidence: 97%
See 1 more Smart Citation
“…; Hopper et al . ). However, our categorization of fungal taxa as plant pathogenic was relatively coarse (i.e.…”
Section: Discussionmentioning
confidence: 97%
“…This further supports a direct role for host-symbiont interactions in driving these patterns, due to the intimate relationship between a tree and its ectomycorrhizal symbionts versus the looser interaction between a tree root and a saprotrophic fungus, for instance. We hypothesized that we would find a biogeographic relationship with pathogenic taxa, as other studies have found evidence of (Zocca et al 2008;Phillips et al 2010;Hopper et al 2014). However, our categorization of fungal taxa as plant pathogenic was relatively coarse (i.e.…”
Section: Host Biogeography and Rhizosphere Fungal Communitiesmentioning
confidence: 91%
“…The depressing effects of disease organisms on host populations following introduction of pathogens to a new area are familiar (e.g. Van Riper et al, 1986;Atkinson et al, 1995;Hochachka & Dhondt, 2000;Hosseini et al, 2006;Ricklefs, 2010b), as are rapid increases of host populations introduced to areas free of host-specific pathogens (Mitchell & Power, 2003;Reinhart et al, 2003;Torchin et al, 2003;Mitchell et al, 2006;Inderjit & van der Putten, 2010;Hopper et al, 2014). However, variations in local population sizes and geographical distributions of native host species rarely have been related to the impacts of native, endemic pathogens (cf.…”
Section: Introductionmentioning
confidence: 99%
“…At larger scales of kilometers or more, the expression of diseases often varies across natural or anthropogenically caused environmental gradients (see Section 7.2 below; Thieltges et al, 2009;Byers et al, 2014;Hopper et al, 2014). For example, Wilson et al (1992) found that spatial and temporal variability in the prevalence and infection intensity of Perkinsus marinus in C. virginica populations in the Gulf of Mexico correlated well with contaminant body burdens.…”
Section: Spatial Variationmentioning
confidence: 99%
“…As this science on host and parasite interactions in the above perspective grew, the perspective expanded, not just on single species parasite-host systems where the host is in essence the 'habitat' (or island, Kuris et al, 1980; but see Lawton et al, 1981) for the parasite, but an ever increasing vision of higher ecological levels of complexity from individuals to even ecosystems. With this expanding interpretation the perspective also expanded spatially, from a single host as a parasite's 'world' to metapopulations, populations, expanding from meters to kilometers and even greater spatial ranges from continents or oceans to global terrestrial, freshwater, and marine biogeographical provinces (e.g., Lafferty et al, , 2010; Morand and Krasnov, 2010;Poulin et al, 2011;Byers et al, 2014;Hopper et al, 2014;. These patterns have been exacerbated significantly by global parasite and host introductions (e.g., Thieltges et al, 2009;Sorte et al, 2010;Sousa et al, 2014).…”
Section: Introductionmentioning
confidence: 99%